ИННОВАЦИОННЫЕ ПОДХОДЫ РАЗВИТИЯ ПРЕДПРИНИМАТЕЛЬСТВА (International Journal of Innovative Technologies in Economy, 2018)
The paper recommends working out a comprehensive state program on innovative development of the Uzbekistan's economy for medium and long term perspective. The framework of equal economic conditions legislatively created for enterprises irrespective of their forms of ownership opens up the possibilities for an unbiased assessment of the advantageous forms of production organization. Competition between enterprises with various forms of ownership encourages the improvement of the internal system of production management, technical retooling, the improvement of the responsiveness to new achievements in science and technology, of manufacturing the better quality goods at low costs and cheaper prices In the long run this proves to be a powerful lever of economic, scientific and technological progress. The issues of the formation of innovative model of small-scale business end entrepreneurship development, elaboration of concrete forms and methods of state regulation of innovations, carried out by entrepreneurial structures that will provide the innovative tendency of national economy are considered in the article.